1997
DOI: 10.1161/01.cir.96.9.2905
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed Intracoronary Hemodynamics in Myocardial Bridging

Abstract: Coronary hemodynamics in myocardial bridges are characterized by a phasic systolic vessel compression with a localized peak pressure, persistent diastolic diameter reduction, increased blood flow velocities, retrograde flow, and a reduced flow reserve. These alterations may explain the occurrence of symptoms and ischemia in these patients. Intracoronary stent placement abolished all hemodynamic abnormalities and may improve clinical symptoms in otherwise unsuccessfully treated patients with myocardial bridges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
80
2
7

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(97 citation statements)
references
References 39 publications
8
80
2
7
Order By: Relevance
“…Several studies have defined MB as coronary artery narrowing of > 50%. [27][28][29] However, we have adopted this less restrictive definition for the following reasons: (1) We usually used the right anterior oblique caudal view to monitor changes in coronary diameter in response to drug infusion. Because MB is frequently present over the mid segment of the left anterior descending coronary arteries (LAD), apparent systolic narrowing of the MB segment may be less in the right anterior oblique caudal view than in the cranial views.…”
Section: Definitionsmentioning
confidence: 99%
“…Several studies have defined MB as coronary artery narrowing of > 50%. [27][28][29] However, we have adopted this less restrictive definition for the following reasons: (1) We usually used the right anterior oblique caudal view to monitor changes in coronary diameter in response to drug infusion. Because MB is frequently present over the mid segment of the left anterior descending coronary arteries (LAD), apparent systolic narrowing of the MB segment may be less in the right anterior oblique caudal view than in the cranial views.…”
Section: Definitionsmentioning
confidence: 99%
“…Three patients studied after coronary stenting had a complete reversal of all hemodynamic abnormalities caused by the myocardial bridge. 17 We propose initial medical therapy and an interventional approach with coronary artery stenting for refractory cases. Before patients proceed to revascularization therapy, objective evidence of ischemia in the territory of the bridge should be documented by some form of objective testing (perfusion imaging, stress echocardiography, or fractional flow reserve measurement by pressure wire).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the myocardial bridges, at the time that peak systolic pulse tends to expand the wall, the 'tunnelled' coronary segment undergoes remarkable compression and lumen radius reduction due to contraction of the surrounding myocardium. Although the blood pressure exhibits a significant increase within the bridged segments compared with the adjacent proximal regions (17), the net effect of these counteracting forces (ie, myocardial compression and blood pressure) is a reduced pressure gradient across the wall of the bridge and subsequently, a decreased TS (8,18), which maintains a normal endothelial function, thereby preventing the development of atherosclerosis (19) (Figure 2). Supporting the atheroprotective effect of low TS within the bridge is the observation that portions of vertebral arteries that are passing through the bone canal are free from atherosclerotic lesions compared with those outside the canal (18).…”
Section: Role Of Tensile Stressmentioning
confidence: 99%
“…Flow analyses proximal, within and distal to the 'tunnelled' artery revealed that within a bridge, there is no anterograde flow during systole, possibly due to myocardial compression ('milking effect'), followed by an accelerated forward flow in diastole (4,17). Conversely, the collapsed bridge generates a retrograde systolic flow at the epicardial segment proximal to the bridge, accompanied by an accelerated forward flow in diastole (4,17).…”
Section: Role Of Tensile Stressmentioning
confidence: 99%
See 1 more Smart Citation